Export Dynamics of Rubber From Like-Minded Countries To European Union - Birka Septy Meliany; Yusman Syaukat; Widyastutik Widyastutik; Amzul Rifin (Jurnal Manajemen dan Agribisnis, 2025)
Background: The European Union is a major importer of natural rubber. However, the rise of global competition and the implementation of the European Union Deforestation Regulation (EUDR) in 2023 has impacted rubber trade dynamics, particularly in Like-Minded Countries (LMC).Purpose: This study analyzes the competitiveness and efficiency of rubber exports from 17 LMC to the European Union from 2013 to 2022.Design/methodology/approach: The study uses Revealed Comparative Advantage, Export Product Dynamics, X-Model, and Stochastic Frontier Analysis with data from the UN Comtrade, Trade Map, and World Bank.Findings/Result: This study shows increased competitiveness in rubber exports to the European Union, while some countries experienced stagnation. The implementation of sustainability policies, particularly the EUDR, significantly influences export competitiveness. Countries that adhere to sustainability standards have demonstrated notable improvements in their export performance. Conclusion: Although some countries have significant export potential, they have not fully optimized it. The LMC needs to enhance efficiency and meet sustainability standards to improve competitiveness and fully leverage export potential in the European Union market.Originality/value (state of the art): This research contributes to the limited literature on rubber trade dynamics under the impact of environmental regulations such as the EUDR. It comprehensively analyzes trade patterns and efficiency and offers valuable insights for academic and practical applications in global trade studies. Keywords: Competitiveness, environmental policy, export efficiency, stochastic frontier, trade potential